2018
DOI: 10.1186/s12917-018-1577-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined plasma rich in growth factors and adipose-derived mesenchymal stem cells promotes the cutaneous wound healing in rabbits

Abstract: BackgroundThe use of Plasma Rich in Growth Factors (PRGF) and Adipose Derived Mesenchymal Stem Cells (ASCs) are today extensively studied in the field of regenerative medicine. In recent years, human and veterinary medicine prefer to avoid using traumatic techniques and choose low or non-invasive procedures. The objective of this study was to evaluate the efficacy of PRGF, ASCs and the combination of both in wound healing of full-thickness skin defects in rabbits. With this purpose, a total of 144 rabbits were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 47 publications
2
28
1
1
Order By: Relevance
“…This also agreed with our observations. Furthermore, MT staining in the study by (Chicharro et al, 2018) [8] came in agreement with our results as it revealed a significant increase in blood vessel formation in PRGF-treated wounds at all studied days compared to control groups. PRGF enhanced collagen deposition at days 1, 2 and 5 compared to control groups.…”
Section: Discussionsupporting
confidence: 93%
“…This also agreed with our observations. Furthermore, MT staining in the study by (Chicharro et al, 2018) [8] came in agreement with our results as it revealed a significant increase in blood vessel formation in PRGF-treated wounds at all studied days compared to control groups. PRGF enhanced collagen deposition at days 1, 2 and 5 compared to control groups.…”
Section: Discussionsupporting
confidence: 93%
“…The human samples were anonymized, and the experimental procedure was previously evaluated and accepted by the Regional Ethics Committee for Clinical Research with Medicines and Health Products following the Code of Practice 2014/01. Rabbit adipose tissue was collected as a surplus tissue from one single individual, a female New Zealand rabbit (8 months old), shortly before sacrifice in the previous study [ 52 ]. Both HADSC (human ADSC) and RADSC (Rabbit ADSC) were isolated, expanded and characterized as previously described [ 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Плазму, збагачену тромбоцитами, виготовляють шляхом відбору зразка крові з різними антикоагулянтами та наступним одночи двоступеневим центрифугуванням, у результаті чого отримують очищену плазму, збагачену тромбоцитами, або плазму, збагачену лейкоцитами та тромбоцитами. Проте присутність антикоагулянтів і необхідність додавання різних речовин як активаторів тромбоцитів можуть викликати негативні реакції організму як неаутологічні продукти (Franklin et al, 2017;Chicharro et al, 2018;Etulain, 2018;Maia et al, 2019). З огляду на це, до переваг PRF зараховують нескладну та швидку техніку його одержання, відсутність необхідності додавання сторонніх речовин, біохімічних обробок, імунних реакцій, передачі інфекційних захворювань, а також поступовий екстрацелю-лярний вихід із тромбоцитів факторів росту протягом семи діб (Kiran et al, 2011;Ayswaria et al, 2018).…”
Section: вступunclassified